#TITLE_ALTERNATIVE# - SANG JIVI PRISWARI (NIM : 13607032); Pembimbing : Dr. Ir. Bambang Kismono Hadi ; Dr. Ir. Ra, AWANG
Wing is one of the most important part on fighter aircraft that serves to generate lift. In addition to generate lift, wing can be used to place the weapon and fuel. With these requirements, the components of wing structure should be able to withstand the load and make sure to avoiding structure failure. In this thesis research, design of wing structure is made based on preliminary design MJK Fighter aircraft and making a comparative study on similar fighter aircraft. The next step is calculate the critical loads applied to the wing structure, in this case the critical loads is the maximum load factor, n=+9. After the load is calculated, some analysis of loading are doing by finite elemen method and evaluate the strength of the structure. To obtain more efficient and actual wing design, the design of the wing structure will be modified. The modifying variable either of thickness of wing component and material used. The final result of this research is wing structure capable of withstanding the critical load evidenced by maximum strees value lower than material yield strength. The addition result of the iteration also generate a more efficient design in terms of weight.